IR SPECTROSCOPY OF MIXED-LIGAND COORDINATION COMPOUNDS OF COBALT(II) ION WITH KETOROLAC (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
This article presents the results of research on the synthesis and analysis of mixed-ligand coordination compounds of cobalt (II) ion with ketorolac and amides. Solvent-based methods were selected for the synthesis process, in which cobalt (II) salts (such as chloride or acetate), ketorolac, and various amides (formamide, acetamide, nicotinamide) reacted in specific molar ratios to form new coordination compounds. To determine the structure and composition of the complexes, IR, UV-Vis, and NMR spectral analyses, as well as elemental analysis and X-ray diffraction (XRD), were employed. Thermal analysis was used to establish the thermal stability of the complexes. During the study, the coordination interactions of ligands with cobalt (II) ions, their electronic configuration, and biological activity were examined, and corresponding conclusions were drawn.